TRAINING YOUNG PEOPLE IN THE SPIRIT OF PATRIOTISM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The Concept of educating young people in the military-patriotic spirit (hereinafter referred to as the Concept) was developed based on the main principles and priorities of the state policy regarding youth implemented in our country, in the current complex globalization era, when information and communication technologies are rapidly developing. current tasks related to educating young people in a military-patriotic spirit and ways to solve them, the role and importance of state and non-state organizations, family, neighborhood, educational institutions in this regard, national and international determines taking into account legal norms.